Natural product diversity associated with the nematode symbionts Photorhabdus and Xenorhabdus. (December 2017) - Tobias, Nicholas; Wolff, Hendrik; Djahanschiri, Bardya; Grundmann, Florian; Kronenwerth, Max; Shi, Yi-Ming; Simonyi, Svenja; Grün, Peter; Shapiro-Ilan, David; Pidot, Sacha; Stinear, Timothy; Ebersberger, Ingo; et al.
Abstract Xenorhabdus andPhotorhabdus species dedicate a large amount of resources to the production of specialized metabolites derived from non-ribosomal peptide synthetase (NRPS) or polyketide synthase (PKS). Both bacteria undergo symbiosis with nematodes, which is followed by an insect pathogenic phase. So far, the molecular basis of this tripartite relationship and the exact roles that individual metabolites and metabolic pathways play have not been well understood. To close this gap, we have significantly expanded the database for comparative genomics studies in these bacteria. Clustering the genes encoded in the individual genomes into hierarchical orthologous groups reveals a high-resolution picture of functional evolution in this clade. It identifies groups of genes—many of which are involved in secondary metabolite production—that may account for the niche specificity of these bacteria.Photorhabdus andXenorhabdus appear very similar at the DNA sequence level, which indicates their close evolutionary relationship. Yet, high-resolution mass spectrometry analyses reveal a huge chemical diversity in the two taxa. Molecular network reconstruction identified a large number of previously unidentified metabolite classes, including the xefoampeptides and tilivalline. Here, we apply genomic and metabolomic methods in a complementary manner to identify and elucidate additional classes of natural products. We also highlight the ability to rapidly and simultaneously identify potentially interesting bioactive products from NRPSs and PKSs, thereby augmenting the contribution of molecular biology techniques to the acceleration of natural product discovery. Comparative genomics and high-resolution mass spectrometry reveal the biosynthetic gene clusters, and vast chemical diversity of natural products that they encode, inPhotorhabdus andXenorhabdus, bacteria that interact with hosts as symbionts and entomopathogens.